Inflation Dynamics in the CEMAC Region - Poplawski Ribeiro, Marcos (IMF Working Papers; Working Paper, 2011)
This paper analyses inflation dynamics in the Central African Economic and Monetary Community (CEMAC) using a constructed dataset for country-specific commodity price indices and panel cointegrated vector autoregressive (VAR) models. Imported commodity price shocks are significant in explaining inflation in the region. Governments are another driving force of inflation dynamics mainly through controlled prices and the role of capital expenditure in domestic activity. In most CEMAC countries, the largest effect of global food and fuel prices occurs after four or five quarters in noncore inflation and then decays substantially over time. Second-round effects are significant only in Cameroon and to a lesser extent in the Republic of Congo.